Pola Komunikasi Orangtua Tunggal Dalam Membentuk Karakter Diri Anak - Khairunnisa Nisa; Muhammad Fariz Al Farisi; Muhammad Firmansyah; Siti Amanah; Elvira Linanda Putri (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
The first communication that will occur in the family environment means Family is very, very influential on the formation of a person's communication patterns in the future. The child in the family will not be separated from the dilemma, especially if both parents decide to live life or divorce, then the child will have a different parenting style. This is the beginning where single parents must be able to establish good communication patterns for children. Character in a person is generally in line with their behavior. The most important thing in family communication is to establish a good and effective communication relationship between parents and children, so that children can understand the gist of the concept even though they have different backgrounds. Because of these things, the author is interested in discussing the issue of single parent communication patterns in shaping children's personal character, where the author uses qualitative research methods. This method shows people's lives, behavior, organizational functionalization, social movements, and kinship relationships. Qualitative research uses a natural setting with the intention of interpreting the phenomena that occur and is carried out by involving various existing methods.